Nigerians' views on national turmoil : a situational quadruple nexus analysis - Badejo, Babafemi Adesina, 1955- (Yintab Books, 2022)
"Nigeria is currently experiencing a complexity of problems. Of particular importance among these are variegated conflicts that have made peace and security very elusive in the country. In almost all of the the six zones making up the country there have been violent acts carried out by terrorists, bandits, ethnic militia as well as the heightened criminal actions of kidnappers and others. Additionally, Nigeria has been a failure with respect to efforts to realise development, respect for human rights, as well as resilience in the handling of humanitarian problems. Encompassing an extensive literature review, interviews with focus groups, as well as a survey of 207 informed Nigerians, this book interrogates and contextualises the importance of the four-pillar interlinkages. More importantly, however, it explores the situational arrangements within which the quadruple nexus or situational four-pillar interlinkages operate. Aside from the qualitative analysis, the study brings into sharp focus the views of informed Nigerians on the current conflicts enveloping Nigeria."--